Simplified reliable online essay test marking for Massive Open Online Course (MOC) using Rasch model analysis / Mohd Nor Mamat … [et al.] - Mamat, Mohd Nor; Temyati, Zawawi; Mahamood, Siti Fatahiyah; Musa, Hanifah (Penerbit UiTM (UiTM Press), 2018)
Manual practice in formal examination does not assess accurate measure of a student’s ability, as it merely counts the score of every question to be considered for the student’s grade. There are many educators who have used raw score as a form of measurement for a student’s ability, but it never truly measures the right measurement. The raw score should be converted into the right linear metrics for ability measurement. This procedure contains measuring score of accurate student’s ability in LOGIT unit, providing of student’s result profile, and measuring reliability of the test set and the student’s answers. The procedure is designed for massive open online learning and paperless essay-based test which is more difficult to be analysed. This procedure converts the student’s answer into rubrical ratio-based scale to be more accurately measured. It is definitely better than the common practice of merely analysis on raw marks for each question. It would show true student’s performance of cognitive performance (test) which represents the true student’s ability (in LOGIT unit), in order to accurately measure the right outcome. This new paradigm of assessment is fit to be applied for massive numbers on online students. It uses Rasch model which offers reliable solution in producing accurate ability marks for students, together with scientific reliability score for student’s answer.